PEMANFAATAN MEDIA PEMBELAJARAN BERBASIS KOGNITIF UNTUK MENINGKATKAN PROSES BERPIKIR SISWA - Marisa Levinda Atamou; Jefan Dreanzy Marjunov Kadjakoro; Ine Setiawati Bani Woli; Rey Matheos Herson Nafie; Yori Madelina Tafuli; Maria Indriani Sesfao (ADIBA : JOURNAL OF EDUCATION, 2025)
The use of cognitive-based learning media is an innovative approach to enhancing students’ thinking processes. This type of media is designed to stimulate cognitive functions such as attention, perception, memory, and problem-solving, all of which play a crucial role in knowledge construction. This study aims to explore the effectiveness of implementing learning media that actively support students' mental engagement. Using a literature review method, data were gathered from various journals, books, and research reports related to cognitive learning theories and the use of educational media. The findings show that cognitive-based media such as interactive simulations, educational videos, and digital applications that require exploration and reflection help students understand concepts more deeply and critically. Additionally, such media foster active student participation, enhance information retention, and develop logical and systematic thinking patterns. Therefore, teachers must have a solid understanding of how to select and integrate appropriate learning media that align with students’ cognitive characteristics and learning needs.